2010
DOI: 10.1088/0953-4075/43/19/194003
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon double ionization of the helium atom by ultrashort pulses

Abstract: Abstract. Two-photon double ionization of the helium atom was the subject of early experiments at FLASH and will be the subject of future benchmark measurements of the associated electron angular and energy distributions. As the photon energy of a single femtosecond pulse is raised from the threshold for two-photon double ionization at 39.5 eV to beyond the sequential ionization threshold at 54.4 eV, the electron ejection dynamics change from the highly correlated motion associated with nonsequential absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
72
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 42 publications
7
72
0
Order By: Relevance
“…The figure clearly shows that the distribution has a backward-forward asymmetry even at the highest intensity considered, demonstrating the breakdown of the single-particle picture, wherein a symmetric double-lobe (dipole) distribution would be found. The results are in accordance with recent results obtained at weaker fields [56,57,63], and shows that the back-to-back ejection mechanism is largely preserved even at very strong fields.…”
Section: Analysis Of Angular and Energy Distributionssupporting
confidence: 92%
See 1 more Smart Citation
“…The figure clearly shows that the distribution has a backward-forward asymmetry even at the highest intensity considered, demonstrating the breakdown of the single-particle picture, wherein a symmetric double-lobe (dipole) distribution would be found. The results are in accordance with recent results obtained at weaker fields [56,57,63], and shows that the back-to-back ejection mechanism is largely preserved even at very strong fields.…”
Section: Analysis Of Angular and Energy Distributionssupporting
confidence: 92%
“…With the ultrashort pulse considered here, the second photon is absorbed before the residual ion has had time to relax to the ground state, but if the duration is increased to beyond 20 cycles, relaxation may occur and a double-peak structure appears (not shown here). The fact that the two peaks, corresponding to sequential two-photon double ionization in the long-pulse limit, shift toward each other in the short-pulse regime and eventually merge into one single peak (located at equal energy sharing) is well known and has been studied in a series of papers in the weak-field (perturbative) limit [33,[56][57][58][59][60][61][62][63][64][65]. The results in Fig.…”
Section: Analysis Of Angular and Energy Distributionsmentioning
confidence: 96%
“…Provided one of the electrons is emitted perpendicular to the laser polarization direction, it is found that the angular distribution of the other electron is characterized by three lobes. The results are similar to those recently reported for the corresponding process in the hydrogen negative ion [R. The problem of direct (nonsequential) two-photon double ionization of helium has been studied extensively in recent years, as exemplified by numerous theoretical [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and experimental [19][20][21][22][23][24] works. This breakup process is fundamental in the sense that it is one of the simplest processes in nature where electron correlations are exhibited, manifested by a rather complex interplay between the electrons.…”
supporting
confidence: 88%
“…The problem of direct (nonsequential) two-photon double ionization of helium has been studied extensively in recent years, as exemplified by numerous theoretical [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and experimental [19][20][21][22][23][24] works. This breakup process is fundamental in the sense that it is one of the simplest processes in nature where electron correlations are exhibited, manifested by a rather complex interplay between the electrons.…”
mentioning
confidence: 99%
“…Comprehensive numerical studies on the DI of helium following the absorption of a few XUV photons were carried out by Parker et al [16] starting 15 years ago. Following the 2005 experiment of Hasegawa et al [7], two-photon DI of helium has been the subject of several theoretical studies [15,[17][18][19][20][21][22][23][24][25][26][27][28]. In particular, Zhang et al [26] calculated joint angular distributions (JADs) for two-photon DI by XUV pulses in both the nonsequential (39.5 eV < ω XUV < 54.4 eV) and the sequential ( ω XUV > 54.4 eV) regimes for different energy sharings of the emitted electrons.…”
Section: Introductionmentioning
confidence: 99%